The magnetism change by Jahn-Teller distortionin octahedral hexa-coordinate complex. Issue 1 (April 2020) - Oguma, Takeyoshi; Tsuneda, Dan; Tsutsumi, Yuki; Fujikawa, Yoshiki; Nakano, Momoe; Ishii, Tomohiko; Sakane, Genta; Ogasaware, Kazuyoshi
Abstract: Metal complexes exhibit significant physical properties such as electrical conductivity, magnetism and optical properties. They can be controlled by changing the ligand field splitting of the d-orbital of the central metal ion. We have investigated the reversible spin crossover (SCO) phenomenon by changing the ligand field splitting in six-coordinated metal complexes ML6 . In this study, we focused on the change of the spin states by uniaxial Jahn-Teller distortion in the case of an octahedral hexa-coordinated metal complexes ML6, involving two types of different ligand molecules. In addition, we have used DV-Xα and DVME methods in order to calculate the electronic states. In order to reproduce the effect of the Jahn-Teller distortion in the calculation, a uniaxial anisotropic distortion has been applied into the octahedral hexa-coordinate metal complex. The purpose of this research is to study the mechanism and phenomenon of the spin state changing by discussing the calculated electronic states of the spin crossover phenomenon.